Copper Recovery From Printed Circuit Boards Using Green Electrolyte - Nur Layli, Wirman (2023)
The evolution of electronic devices has seen remarkable development and continuous improvement in technologies, but their increased use comes an increase in the amount of e-waste produced. This has become an emerging problem for both global and local societies. However, valuable metals make up the majority of e-waste components, making urban mining through electrolysis a feasible method for extracting copper. This study aimed to determine the optimum reaction time current needed for this process. It was found that electrolysis using green electrolyte, which operates at room temperature and atmospheric pressure, yielded the highest extraction of copper at 85% with a reaction time of 3 hours and a current of 1.0 mA. In conclusion, recovering copper through electrolysis using a green electrolyte is more environmentally friendly alternative than virgin mining.